Nutrition and supplementation in football - practical guidelines based on current literature review - Wiktoria Staśkiewicz (Kazimierz Wielki University, 2022)
It is said that football matches are the second most important thing in the world. Football is currently one of the most popular sports and brings record numbers of people together in stadiums and in front of TV sets. For many years, players were allowed to consume the products they preferred at the times they subjectively deemed appropriate. However, today's soccer has evolved due to self-improvement and players following elite athletes. This change in approach to the sport has coincided with an increase in the pace and intensity of top soccer games over the past two decades. In addition, the commercialization of the sport has resulted in increasing demands and continually increasing the level of sportsmanship. Nutrition is an important part of the sports training program. International guidelines, based on scientific research, recommend amounts, types and timing of food intake to ensure excellent training while reducing injuries and trauma. In order to achieve metabolic optimization, there must be a balance between nutrition, training, and recovery. Energy should be provided from optimal sources, and maintaining an adequate energy balance is critical for those who engage in physical activity, especially professional athletes. Supplements and foodstuffs for special nutritional purposes are widely used, so knowledge of the indications for their use, as well as the risks posed by inappropriate use, is essential.